2017
DOI: 10.1038/pr.2017.268
|View full text |Cite
|
Sign up to set email alerts
|

Development of severe bronchopulmonary dysplasia is associated with alterations in fecal volatile organic compounds

Abstract: BackgroundThe aim of this study was to evaluate the potential of fecal volatile organic compounds (VOCs), obtained by means of an electronic nose device (Cyranose 320), as early non-invasive biomarker for BPD.MethodsIn this nested case-control study performed at three Neonatal Intensive Care Units, fecal samples obtained at postnatal age of 7, 14, 21, and 28 days from preterm infants with severe bronchopulmonary dysplasia (BPD) were compared with fecal VOC profiles from matched controls. Microbiota analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…Fecal VOCs are considered to reflect microbiota composition, function, and interaction with the host. 1 , 2 They are increasingly considered to have potential as a biomarker in the diagnostic workup and monitoring of various gastrointestinal diseases, e.g., inflammatory bowel disease (IBD), colorectal cancer, and even sepsis. 3 11 Various studies have demonstrated the diagnostic potential of VOCs in both pediatric and adult IBD populations by analyzing VOCs deriving from urine, exhaled breath, and feces.…”
mentioning
confidence: 99%
“…Fecal VOCs are considered to reflect microbiota composition, function, and interaction with the host. 1 , 2 They are increasingly considered to have potential as a biomarker in the diagnostic workup and monitoring of various gastrointestinal diseases, e.g., inflammatory bowel disease (IBD), colorectal cancer, and even sepsis. 3 11 Various studies have demonstrated the diagnostic potential of VOCs in both pediatric and adult IBD populations by analyzing VOCs deriving from urine, exhaled breath, and feces.…”
mentioning
confidence: 99%
“…The microbiome of breast milk can be "regrown" in pasteurized DHM with the inoculation of unprocessed MOM [58] which awaits clinical testing. BPD has also been associated with changes in the microbiome of the airways [59,60] and may even be associated with the gut microbiome [61].…”
Section: Discussionmentioning
confidence: 99%
“…Infants who survive BPD commonly suffer from impaired cognitive functions and lung function abnormalities. Early identification of preterm infants at risk of developing BPD, allows for timely initiation of interventions [13]. Since BPD is a lung disease, exhaled VOCs may be preferred to perform VOC analysis, however, infants suffering from BPD are commonly mechanically ventilated which makes collection of exhaled breath complicated.…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Several studies have demonstrated the existence of vital cross-talks between different mucosal sites of the body, including bidirectional interaction between gut and lungs, the so-called gut-lung axis [75,76]. Therefore, Berkhout et al aimed to evaluate the potential of fecal VOC by means of eNose (Cyranose 320 ® ) as early non-invasive biomarker for BPD [13]. Fecal VOC profiles were identified at four different time points (7,14,21, and 28 days postnatally) of 15 preterm infants with severe BPD and 15 matched healthy controls.…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
See 1 more Smart Citation